Deconstructing the dogma of domesticity: Quaker education and nationalism in british mandate palestine - Othman, Enaya Hammad; Öney, Celal (Muhammed Mustafa KULU, 2022)
This paper focuses on the Friends Girls School (FGS) in Ramallah as a site of interaction between Americans and Palestinians during the British Mandate between 1920 and 1947. It draws on extensive archival records as well as Palestinian students' writings and oral accounts to trace how Quakers' education and the nationalist discourse in the country influenced the students' personal and national identities. Palestinian students utilized Quaker education as a springboard for the subversion of gendered religious, political and Orientalist discourses which were prevalent during this time period. © 2022, Muhammed Mustafa KULU. All rights reserved.
Ev İçi Dogmanın Yapı Sökümü: İngiliz Mandası Filistin’inde Quaker Eğitimi ve Milliyetçilik
Keywords: British Mandate; Missionary; Nationalism; Ottoman; Palestine; Quaker; Ramallah